Social Capital Mediates the Association between the ICT Usage and Well-Being of Older People in Japan: Implication for a New Design Paradigm - Kokubun, Keisuke; Ogawa, Toshimi; Browne, Ryan; Shinada, Takamitsu; Granrath, Lorenz; Moeller, Johanna; Tram, Nhu; Wieching, Rainer; Taki, Yasuyuki (Sustainability, 2022)
As the population ages, the question of how to prevent isolation among older people and increase their well-being becomes a social issue. It has often been argued that Information and Communication Technology (ICT) usage can be a solution to these challenges, but empirical studies have not shown consistent results. Moreover, there are even fewer studies targeting older people in Japan, which is the most aging country in the world. Therefore, using the psychological comprehensive data of Japanese people aged 60 and over recorded in World Values Survey Wave 7, we conducted a study to clarify the relationship between the ICT usage, social capital, and well-being of older people to make a meaningful contribution to policymakers and the scientific community. As a result of the analysis, it was shown that ICT usage indirectly enhances well-being by increasing social capital. This indicates that for older people, ICT usage does not have a large effect on enhancing well-being, but becomes sufficiently large only through the improvement of social capital. The pros and cons of such modern communication means should be utilized as a reference when considering the development of future communication means and a human coach—a person who supports the use of communication means by older people. In other words, to think about the spread of communication means to community-dwelling older people in the future, it is always necessary to think about technology usage emphasizing the relationship between older people and society.